2021
DOI: 10.1051/e3sconf/202131601006
|View full text |Cite
|
Sign up to set email alerts
|

Market Integration: How Does It Work in National Shallot Commodity Market in The Middle of Covid-19 Pandemic?

Abstract: The impact affected by the covid–19 pandemic influences various sectors in Indonesia, with no exception in agriculture sector. However, the agriculture sector still becomes a sustaining sector for other economic sectors because society's necessity is fulfilled by agriculture. Shallot is one of seven important commodities as basic needs for Indonesian and horticulture primadonna. Covid–19 pandemic presence influences shallot marketing indirectly from farmer till modern market. This research was conducted to ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 21 publications
0
3
0
2
Order By: Relevance
“…The results showed that the shocks experienced by shallot farmers in Tapin Regency related to marketing difficulties occurred from 2015 to 2017, which caused shocks to shallot farmers in the area (Eka et al, 2017). For most farmers during a simultaneous harvest, the marketing of shallots is very difficult, and the price drops lower due to the abundant stock or supply of shallots (Destiarni et al, 2021). In addition, it is also difficult for local shallots to compete with shallots brought in from outside the region (Java Island), and it is difficult to enter the market because large markets such as the central market in Banjarmasin are already controlled by traders who import shallots from outside the island (Eka et al, 2017;Susanawati et al, 2015).…”
Section: Shock Analysismentioning
confidence: 99%
“…The results showed that the shocks experienced by shallot farmers in Tapin Regency related to marketing difficulties occurred from 2015 to 2017, which caused shocks to shallot farmers in the area (Eka et al, 2017). For most farmers during a simultaneous harvest, the marketing of shallots is very difficult, and the price drops lower due to the abundant stock or supply of shallots (Destiarni et al, 2021). In addition, it is also difficult for local shallots to compete with shallots brought in from outside the region (Java Island), and it is difficult to enter the market because large markets such as the central market in Banjarmasin are already controlled by traders who import shallots from outside the island (Eka et al, 2017;Susanawati et al, 2015).…”
Section: Shock Analysismentioning
confidence: 99%
“…Setidaknya terdapat tiga alasan yaitu: (1) bawang merah merupakan bagian dari subsektor hortikultura yang berpotensi untuk dikembangkan sebagai pembangunan baru pada sektor pertanian dan berpotensi meningkatkan Produk Domestik Bruto (PDB) nasional; (2) pengembangan produksi mendukung upaya peningkatan ketahanan pangan dan ketersediaan pangan; (3) perubahan harga yang relatif cepat dapat menyebabkan inflasi yang akan berdampak buruk bagi perekonomian Indonesia (Magfiroh et al, 2017). Dengan demikian, sebagai jenis komoditi strategis nasional, bawang merah akan selalu mendapat perhatian khusus dari pemerintah dan pelaku usaha terkait dengan peranannya dalam memengaruhi kondisi ekonomi, politik, dan sosial masyarakat (Destiarni et al, 2021) potensial ke depannya baik dalam bentuk usaha tani (on-farm) maupun dalam bentuk usaha di luar usaha tani (off-farm). Irawan (2007) menjelaskan bahwa pengembangan hortikultura pada umumnya lebih banyak dijumpai pada bentuk off-farm, terutama pada penanganan pascapanen dan pemasaran.…”
Section: Pendahuluanunclassified
“…Sebaliknya pada bulan Maret-Juni ketika produksi cabai berlimpah, harga cabai rawit menjadi rendah. Hal ini sesuai dengan yang dikemukakan oleh (Destiarni, Zainuddin, & Jamil, 2021;Jumiana, Azhar, & Marsudi, 2018) bahwa komoditas hortikultura dari jenis sayuran merupakan produk yang paling sering mengalami fenomena fluktuasi harga karena permintaannya terjadi secara terus menerus sepanjang tahun sedangkan pola produksinya bersifat musiman.…”
Section: Gambar 1 Harga Rata-rata Bulanan Cabai Rawit DI Indonesia Ta...unclassified